Health Care Workers’ Perceived Self-Efficacy to Manage COVID-19 Patients in Central Uganda: A Cross-Sectional Study - Najjuka SM; Ngabirano TD; Balizzakiwa T; Nabadda R; Kaggwa MM; Kateete DP; Kalungi S; Beyeza-Kashesya J; Kiguli S (Dove Medical Press, 2022)
Sarah Maria Najjuka,1 Tom Denis Ngabirano,2 Thomas Balizzakiwa,1 Rebecca Nabadda,1 Mark Mohan Kaggwa,3 David Patrick Kateete,4 Samuel Kalungi,5 Jolly Beyeza-Kashesya,6 Sarah Kiguli7 1College of Health Sciences, Makerere University, Kampala, Uganda; 2Department of Nursing, College of Health Sciences, Makerere University, Kampala, Uganda; 3Department of Psychiatry, Mbarara University of Science and Technology, Mbarara, Uganda; 4Department of Immunology and Molecular Biology, College of Health Sciences Makerere University, Kampala, Uganda; 5Department of Pathology, Mulago National Referral Hospital, Kampala, Uganda; 6Department of Obstetrics and Gynecology, Mulago Specialized Women and Neonatal Hospital, Kampala, Uganda; 7Department of Pediatrics and Child Health, School of Medicine, College of Health Sciences, Makerere University, Kampala, UgandaCorrespondence: Sarah Maria Najjuka, College of Health Sciences, Makerere University, Kampala, Uganda, Email najjukasarah@gmail.comBackground: The novel coronavirus disease 2019 (COVID-19) pandemic placed health workers at the frontline of the emergency task force response; a duty that requires professional expertise and confidence to rapidly identify and treat patients with COVID-19. This study explored perceived self-efficacy (PSE) of health care workers (HCWs) in the management of patients with COVID-19 and associated factors in central Uganda.Methods: We recruited 418 HCWs from four national referral hospitals in Uganda. Multivariate linear regression analysis was utilized to determine factors associated with PSE. A p-value > 0.05 was considered statistically significant.Results: Majority of the participants were female, about half were nurses/midwives, and had 10 years of work experience on average. Overall, HCWs reported moderate PSE in managing COVID-19 patients which reduced with increasing severity of the COVID-19 illness. Having a PhD, being a medical doctor, agreeing or completely agreeing that one has knowledge about COVID-19 management, and having COVID-19 management training were significantly associated with increase in one's level of PSE.Conclusion: This study highlights an unsatisfactory, moderate level of PSE among HCWs in the management of patients with COVID-19 in central Uganda. The health sector should focus on improving HCWs' self-efficacy through continuous training of all HCWs in the clinical management of especially the severe and critically ill cases of COVID-19. Non-doctor HCWs should be given priority as they scored lower levels of PSE; yet they are the corner stone of the primary health care system and make majority of the health human resource in low- and middle-income countries. Interventions towards creating a safe working environment for HCWs through provision of adequate infection prevention and control strategies are essential in boosting HCWs confidence to manage COVID-19 patients.Keywords: perceived self-efficacy, COVID-19, Uganda, health care workers, COVID-19 knowledge, COVID-19 management, COVID-19 training